INTEGRATIVE FRAMEWORK FOR COLLABORATIVE SOCIAL INNOVATION FROM THE RONDON PROJECT (Desenvolvimento em Questão, 2020)
In the research area of social innovation, is essential to understand the process of generating value and how the interactions between the actors can generate something innovative. The aim of this article is to characterize the dynamics of an integrative framework of social innovation through the collaborative relations of the Rondon Project. An integrative theoretical framework was developed, based on the analysis of the literature, composed of four dimensions of analysis - social challenges, process, networks and results. The data collection used a qualitative approach, through in-depth interviews and focus groups with 38 participants of the Rondon Extension Project at the State University of Santa Catarina, public managers and from Rancho Queimado´s community. It is evident that the university enables the strengthening of collaborative networks between actors and co-creative practices imply mutual social value, favoring the sharing of knowledge and resources. In an initial effort to build a systemic vision, it was understood that to move towards a new paradigm of social innovation it is necessary to encourage collaborative, intersectoral and inclusive models, in order to provide innovative solutions that effectively generate value in solving social problems. Finally, future research is recommended for advances in the theme of social innovation.
Keywords: Social Innovation; Collaboration; Integrative Approach.